New Paleomagnetic Constraints on the Early Cretaceous Paleolatitude of the Lhasa Terrane (Tibet) - Li, Zhenyu; Ding, Lin; Laskowski, Andrew K.; Burke, William B.; Chen, Yaofei; Song, Peiping; Yue, Yahui; Xie, Jing (Frontiers in Earth Science, 2022)
New zircon U-Pb dating results from the Zonggei Formation volcanics indicate that the volcanic rocks formed at ∼114–110 Ma. Paleomagnetic data, petrography, and rock magnetism confirm the primary nature of isolated characteristic remanent magnetizations carried by titanomagnetite and hematite. A statistical analysis of the combined results from the Zonggei and Duoni formations reveals a group-mean direction of D±ΔD = 0.4° ± 6.0°, I±ΔI = 22.2° ± 5.6°, α95 = 5.6°, k = 35.2 after bedding correction based on 20 group-mean directions. The corresponding paleopole was calculated to be λp = 70.3°N, φp = 270.5°E with A95 = 5.2°. The interpretation of our data alongside the Cenozoic data from the Tethyan Himalaya indicates that the India–Asia collision initiated by 61.7 ± 3.0 Ma at 13.0° ± 1.8°N, assuming a single-collision model. Intracontinental crustal shortening totaling 1,770 ± 470 km took place on the Asian side since the onset of India–Asia collision. Furthermore, the data show that the Neo-Tethys Ocean reached its maximum N-S width of 7,100 ± 530 km at ∼132 Ma and shrank to 6,400 ± 550 km by ∼115 ± 5 Ma. This is consistent with previous estimates based on the geophysical images of the subducted Neo-Tethyan slab beneath Eurasia.